Colistin plus meropenem for carbapenem-resistant Gram-negative infections: in vitro synergism is not associated with better clinical outcomes. (September 2020) - Nutman, Amir; Lellouche, Jonathan; Temkin, Elizabeth; Daikos, George; Skiada, Anna; Durante-Mangoni, Emanuele; Dishon-Benattar, Yael; Bitterman, Roni; Yahav, Dafna; Daitch, Vered; Bernardo, Mariano; Iossa, Domenico; et al.
Abstract: Objectives: In vitro models showing synergism between polymyxins and carbapenems support combination treatment for carbapenem-resistant Gram-negative (CRGN) infections. We tested the association between the presence of in vitro synergism and clinical outcomes in patients treated with colistin plus meropenem. Methods: This was a secondary analysis of AIDA, a randomized controlled trial comparing colistin with colistin–meropenem for severe CRGN infections. We tested in vitro synergism using a checkerboard assay. Based on the fractional inhibitory concentration (ΣFIC) index for each colistin–meropenem combination, we categorized results as synergistic, antagonistic or additive/indifferent. The primary outcome was clinical failure at 14 days. Secondary outcomes were 14- and 28-day mortality and microbiological failure. Results: The sample included 171 patients with infections caused by carbapenem-resistant Acinetobacter baumannii ( n  = 131), Enterobacteriaceae ( n  = 37) and Pseudomonas aeuruginosa ( n  = 3). In vitro testing showed synergism for 73 isolates, antagonism for 20 and additivism/indifference for 78. In patients who received any colistin plus meropenem, clinical failure at 14 days was 59/78 (75.6%) in the additivism/indifference group (reference category), 54/73 (74.0%) in the synergism group (adjusted odds ratio (aOR) 0.76, 95% CI 0.31–1.83), and 11/20 (55%) in the antagonism group (aOR 0.77, 95% CI 0.22–2.73). There was no significant difference between groups for any secondary outcome. Comparing the synergism group to patients treated with colistin monotherapy, synergism was not protective against 14-day clinical failure (aOR 0.52, 95% CI 0.26–1.04) or 14-day mortality (aOR1.09, 95% CI 0.60–1.96). Discussion: In vitro synergism between colistin and meropenem via checkerboard method did not translate into clinical benefit.